Penerapan Teori Penetrasi Sosial dalam Analisis Komunikasi Interpersonal Keluarga Non-Biologis pada Family by Choice - Putri , Cindyka Ardelia; Ike Desi Florina; Sarwo Edy (KOMUNIKA, 2025)
This research aims to analyze the dynamics of interpersonal communication within non-biological families through the Korean drama "Family by Choice," using the Social Penetration Theory by Altman and Taylor as an analytical framework. The phenomenon of non-biological families is increasingly common in society due to several factors. Therefore, interpersonal communication is essential to foster self-disclosure and emotional closeness in the process of relationship development. The drama "Family by Choice" represents the communication processes in non-biological families as a reflection of this social phenomenon. This qualitative study employs documentation techniques, and the findings are analyzed through a process of categorization and interpreted according to the stages of relationship development: orientation, exploratory effective, effective, and stable. The results show the development of relationships among characters in accordance with these theoretical stages, beginning with general and awkward conversations, personal information disclosure, involving feedback and suggestions on discussed topics, until achieving emotional closeness and high trust. These findings illustrate how interpersonal communication in media is portrayed based on real processes in social life. This research reinforces the relevance of social penetration theory as a communication analysis tool in audiovisual works and contributes to the development of studies on interpersonal communication and representations in popular media.